Effects of nursery container size and shape on Acacia tortilis and Faidherbia albida seedling development - Louw, Vincent G.(Vincent George) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.